REKONSEPTUALISASI PENDIDIKAN TINGGI ISLAM DI DAERAH DALAM PERSPEKTIF PAULO FREIRE - Silahuddin Silahuddin; Syamsul Rijal; Randi Muhammad Gumilang (STAI Sangatta Kutai Timur, 2023)
This research aims to reconceptualize Islamic higher education in the region from Paulo Freire's perspective. The focus is on Paulo Freire's educational philosophy, the portrait of higher education in the region, and its reconstruction. The method used in this research is the library research method. The results showed the Freire's formulation of educational philosophy is that education introduced as the education for the oppres, namely educational system is constructed mutually with the oppressed them selves. The education system used to negate an education system which was oriented towards mastery or dominance. Awareness is the core of philosophical process offered by Freire because its human liberation and humanization can only be carried out if individuals or groups in a society are real aware of the reality of themselves and the world around them. Constructively, Islamic higher education in the regions is expected to be able to reorient towards quality aspects that go hand in hand with accessibility, which is a main part of regional government programs in the context of investing in human resources. Furthermore, the higher education curriculum is expected to be able to accommodate contemporary developments through the principles of independent learning on independent campuses by prioritizing the basic principles of humanist education, as in Paulo Freire's educational philosophy.